Integrating Character and Learning Outcomes Through the Archerys ID Model in Elementary IPAS Learning: Supporting SDG 4 - Desi Engriani; Darmansyah; Zelhendri Zen; Rayendra (Postgraduate, University of Mataram, 2026)
This study aims to examine the effect of the Archerys Instructional Design (ID) Model on students’ moral understanding, academic ethics, and IPAS learning outcomes among sixth-grade students at SDN 04 Korong Kota Solok. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 40 students divided into two intact classes, namely an experimental class receiving instruction through the Archerys ID Model and a control class receiving conventional learning instruction. Data were collected using questionnaires to measure moral understanding and academic ethics, essay tests to measure IPAS learning outcomes, observation sheets, and interviews as supporting qualitative data. Quantitative data were analyzed using descriptive statistics, normality tests, homogeneity tests, Multivariate Analysis of Variance (MANOVA), and Independent Sample t-tests. The results indicated significant differences between the experimental and control groups across all dependent variables (p < 0.05). Students in the experimental class achieved higher average scores in moral understanding (84.20) compared to the control class (74.10), academic ethics (84.50 compared to 73.20), and learning outcomes (87.80 compared to 77.40). In addition, correlation analysis demonstrated a positive trend in the relationship between moral understanding, academic ethics, and learning outcomes following the implementation of the Archerys ID Model, although the correlation strength remained statistically weak. These findings indicate that the Archerys ID Model effectively supports the integration of affective and cognitive learning dimensions through meaningful and value-oriented instructional activities in elementary school IPAS learning contexts.